Prospects and Challenges of Ecotourism Sector and Poverty Eradication in Sabah: The Case of Orangutans and Mabul Island - Mayan, Siti Nor ‘Ain; Nor, Radieah Mohd (Global Journal of Social Sciences Studies, 2017)
Ecotourism is a nature-based tourism in Malaysia with a high growth potential. In terms of biodiversity, Malaysia is ranked 12th in the world. Hence, Malaysia has attracted tourists across the world, especially to Sabah. The orangutans, the beach and the underwater beauty of Mabul Island have the potential of turning Semporna and Sandakan in Sabah to become ecotourism centres in Malaysia. However, Sabah has remained as the poorest state in Malaysia. Using secondary data, this study examines the challenges faced by the locals in their efforts to improve their lives through their ecotourism sector. The locals faces challenges such as domination of business by outsiders and their lack of skills, capital and interest in entrepreneurship. Hence this study will suggest some solutions on how to overcome these challenges facing the locals in the two study areas.